Yuck! Plural Valuation of Constructed Wetland Maintenance for Decentralized Wastewater Treatment in Rural India - Friedrichsen, Claire N.; Monroe, Martha C.; Daroub, Samira H.; Wani, Suhas P. (Frontiers in Sustainable Food Systems, 2021)
In 2012, an estimated 50% of rural households in India had a system of drainage for moving wastewater away from their homes, but 0.0% have access to safe, reuseable, treated wastewater. Constructed wetlands can provide decentralized wastewater treatment for rural villages and lead to multiple benefits, such as reusable water, reduced disease, and decreased environmental pollution. However, the maintenance of decentralized wastewater technologies is poorly understood. We used a case study design across four communities and six constructed wetlands to understand the social and cultural variables impacting the maintenance of constructed wetlands for decentralized wastewater treatment to provide agricultural irrigation water. Semi-structured interviews (n=39) and focus groups (n=4) were conducted with people from Telangana and Karnataka, India. Interviewees were classed into four groups: (1) Scientists, (2) Farmers, (3) Privileged Community Members, and (4) Socially Disadvantaged Community members. Inductive, constant comparison qualitative data analysis was used to develop a model for explaining the existing practice of wetland maintenance. Three themes emerged from the data: mental models of constructed wetland maintenance show plural valuation of ecosystem services, yuck as a leverage point for decreasing social cohesion in the community, and recommendations for improving maintenance through human-centered design. Based on the results, we propose a model for understanding how to incorporate the plural valuation of ecosystem services provided by constructed wetlands and human-centered design to support long-term adoption and maintenance of decentralized wastewater treatment technologies.